2008
DOI: 10.1111/j.1365-246x.2007.03683.x
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary study of a slow-slipping fault for seismic hazard assessment: the example of the Middle Durance Fault (SE France)

Abstract: SUMMARY Assessing seismic hazard in continental interiors is difficult because these regions are characterized by low strain rates and may be struck by infrequent destructive earthquakes. In this paper, we provide an example showing that interpretations of seismic cross sections combined with other kinds of studies such as analysis of microseismicity allow the whole seismogenic source area to be imaged in this type of region. The Middle Durance Fault (MDF) is an 80‐km‐long fault system located southeastern Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 53 publications
(88 reference statements)
5
96
0
Order By: Relevance
“…Most of the earthquakes are confined to the upper 10 km of the crust; however, as noted by Cushing et al [14], a few seismic events are located deeper than the sedimentary cover. These deep earthquakes could be linked to potentially seismogenic blind thrusts within the pre-Triassic basement.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most of the earthquakes are confined to the upper 10 km of the crust; however, as noted by Cushing et al [14], a few seismic events are located deeper than the sedimentary cover. These deep earthquakes could be linked to potentially seismogenic blind thrusts within the pre-Triassic basement.…”
Section: Discussionmentioning
confidence: 88%
“…[14]: a) the P-wave velocity of each layer is the area weighted average of the velocity sampled at that depth interval by the data; b) the topmost layer and the station corrections reflect the basic features of near-surface structure; c) equally high precision locations should be found for all well-locatable earthquakes occurring anywhere within the seismic network.…”
Section: Introductionmentioning
confidence: 99%
“…The reach between Mirabeau and Sisteron has the complete range of terraces revealing increased elevations upstream. This reach attracted earlier terrace studies [43,49,50] and it has been affected by recent tectonics [16,17,24,38,[51][52][53][67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the basement rocks are much closer to the surface east of the MDF [48], implying an initial down throw to the west, it has been suggested that there was reverse uplift on the west side to trap the Miocene Valensole conglomerates [53]. However, to the south between Manosque and Mirabeau, conglomerates are found west of MDF [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation